Dysregulation of Lipid Metabolism in Macrophages Is Responsible for Severe Endotoxin Tolerance in FcgRIIB-Deficient Lupus Mice - Jaroonwitchawan, Thiranut; Visitchanakun, Peerapat; Dang, Phi Cong; Ritprajak, Patcharee; Palaga, Tanapat; Leelahavanichkul, Asada (Frontiers in Immunology, 2020)
FcgRIIB dysfunction is commonly found in patients with lupus, especially in Asia. LPS-tolerance is prominent in FcgRIIB–/– lupus mice. LPS-tolerant macrophages demonstrate cell energy depletion, which might affect lipid metabolism. Therefore, to explore lipid metabolism, LPS-tolerance was induced twice by LPS administration in macrophages and in mice. LPS-tolerant FcgRIIB–/– macrophages demonstrated lesser mitochondrial DNA (mtDNA), more severe ATP depletion, lower cytokine production, and higher lipid accumulation (oil red O staining) compared to LPS-tolerant WT cells. Mass-spectrometry-based lipidomic analysis demonstrated a higher abundance of phosphatidylethanolamine (PE) phospholipid in LPS-tolerant FcgRIIB–/– macrophages than WT cells. This was at least in part due to the lower expression of phosphatidylethanolamine N-methyltransferase (pemt), an enzyme that converts PE to phosphatidylcholine (PC). Aminoimidazole-4-carboxamide ribonucleotide (AICAR), a pemt inhibitor, worsens LPS-tolerance in WT macrophages and supports the impact of pemt upon LPS-tolerant FcgRIIB–/– macrophages. Additionally, phosphorylated AMP-activated protein kinase (AMPK-p), a molecule for ATP-restoration associated with pemt, and phosphorylated acetyl CoA carboxylase, a downstream signaling of AMPK-p, were higher in LPS-tolerant FcgRIIB–/– macrophages than WT. Furthermore, Compound C, an AMPK inhibitor, attenuated LPS-tolerance in both FcgRIIB–/– macrophages and mice. Taken together, the intense decrease in cytokine production after the second LPS stimulation (LPS-tolerance) in FcgRIIB–/– macrophages was possibly due to the impact of an immense cytokine synthesis after the first dose of LPS. This includes using up PEMT, an enzyme of phospholipid synthesis during cytokine production, and AMPK-p induction in response to profound ATP-depletion. Therefore, the manipulation of the AMPK/PEMT axis provides a novel therapeutic candidate for the treatment of severe LPS-tolerance in lupus.